O olhar do professor e dos alunos do ensino médio sobre o currículo de educação física do estado de São Paulo - Bonato, Neusa Aparecida Mendes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Education policies for Basic Education in Brazil, since the LDBEN # 9394/96 promulgation, have brought along significant changes, like the extension of obligatory attendance to all schooling stages, the implementation of school and students assessment systems, as well as guidelines and curriculum documents that propose a national common ground. In order to develop this study, we have addressed theoretical approaches to the curriculum field and the educational policies that form the curricular bases for Secondary School. In addition, we have situated Physical Education historically, as well as its connections to the school institution. In line with such changes, Secondary School has gained prominence in recent years, with offer and obligation extension, besides the search for a new identity, aiming at improving the quality of teaching. The research's aim was to analyse the Secondary School Physical Education Curriculum in São Paulo State, implemented in 2010, verifying all its practical implications in three grades at a state school in the city of Araraquara (SP), according to the teachers' and the students' view over the Curriculum and the didactic material: the Teacher and Student Notebooks. The participants were: one Physical Education teacher and 84 Secondary School students. Results suggest that Secondary School represents a phase of preparing for entering higher education and labour market for most of the participating students. There was a demand for other contents/themes besides sports. Many students pointed out ENEM in their answers and the knowledge presented in the Curriculum can help them with that test. They gave critical opinions about multiple aspects related to the lessons, such as the Physical Education Curriculum, material conservation and material absence. In the teacher's opinion, the activity that started in 2008 with the Students Journal (Jornal do Aluno) has brought up obstacles among students and their parents ...

Las políticas educacionales para la Educación Básica en Brasil desde la promulgación de la LDBEN nº 9394/96 trajeron cambios significativos como la ampliación de la obligatoriedad para todas las etapas de la escolarización, la implementación de sistemas de evaluación de las escuelas y de los alumnos, bien como las directrices y documentos curriculares que proponen una base nacional común. Para la construcción de este estudio, atravesamos los abordajes teóricos sobre el campo del currículo, las políticas educacionales que construyen las bases curriculares para la Enseñanza Secundaria y situamos históricamente la Educación Física y sus vínculos con la institución escolar. Con esos cambios, la Enseñanza Secundaria pasó a ganar evidencia en los últimos años, con la ampliación de la oferta y obligatoriedad y la búsqueda de una identidad propia, con vistas a mejorar la calidad de la enseñanza. Esta investigación objetivó analizar el Currículo de Educación Física de la Enseñanza Secundaria del Estado de São Paulo implantado en el año de 2010, verificando las implicaciones prácticas en tres años de una Escuela Estadual de la ciudad de Araraquara SP, en la visión de los profesores y alumnos sobre el Currículo y los materiales didácticos: Cuadernos del Profesor y del Alumno. Fueron participantes: una profesora de Educación Física y 84 alumnos de la Enseñanza Secundaria. Los resultados sugieren que para la mayoría de los alumnos de este estudio, la Enseñanza Secundaria representa una fase de preparación para el ingreso en la enseñanza superior y la inserción en el mercado de trabajo. Hubo reivindicación de otros contenidos/temas para además de los deportes. El ENEM es visto bajo una heterogeneidad de respuestas y los conocimientos presentados en el Currículo pueden ayudarles en estos exámenes. Opinaron críticamente sobre diversos aspectos que se relacionan con las clases, como el Currículo de Educación ...

As políticas educacionais para a Educação Básica no Brasil desde a promulgação da LDBEN 9394/96 trouxeram mudanças significativas como a ampliação da obrigatoriedade para todas as etapas da escolarização, a implementação de sistemas de avaliação das escolas e dos alunos, bem como as diretrizes e documentos curriculares que propõem uma base nacional comum. Para a construção deste estudo, perpassamos as abordagens teóricas sobre o campo do currículo, as políticas educacionais que constroem as bases curriculares para o Ensino Médio e situamos historicamente a Educação Física e seus vínculos com a instituição escolar. Na esteira dessas mudanças, o Ensino Médio passou a ganhar destaque nos últimos anos, com a ampliação da oferta e obrigatoriedade e a busca de uma identidade própria, com vistas a melhorar a qualidade do ensino. Esta pesquisa objetivou analisar o Currículo de Educação Física do Ensino Médio do Estado de São Paulo implantado no ano de 2010, verificando as implicações práticas em três séries de uma Escola Estadual da cidade de Araraquara SP, na visão dos professores e alunos sobre o Currículo e os materiais didáticos: Cadernos do Professor e do Aluno. Foram participantes: uma professora de Educação Física e 84 alunos do Ensino Médio. Os resultados sugerem que para a maioria dos alunos deste estudo, o Ensino Médio representa uma fase de preparação para o ingresso no ensino superior e a inserção no mercado de trabalho. Houve reivindicação de outros conteúdos/temas para além dos esportes. O ENEM é visto sob uma heterogeneidade de respostas e os conhecimentos apresentados no Currículo podem auxiliá-los nesta provas. Opinaram criticamente sobre diversos aspectos que relacionam-se com as aulas, como o Currículo de Educação Física, o estado de conservação dos materiais e a falta destes. Para a Professora, a ação iniciada com o Jornal do Aluno no ano de 2008 trouxe entraves...
The secondary school teacher and students view on the physical education curriculum in São Paulo state
Keywords: Educação - São Paulo (Estado); Ensino médio - São Paulo (Estado); Ensino - Curriculo - São Paulo (Estado); Educação fisica - Ensino - São Paulo (Estado); São Paulo (Estado) - Educação; Education